2011
DOI: 10.4236/pp.2011.23029
|View full text |Cite
|
Sign up to set email alerts
|

Design, Formulation and Evaluation of Transdermal Drug Delivery System of Budesonide

Abstract: Budesonide is a highly potent synthetic, nonhalogenated corticosteroid. The mechanism of action of corticosteroids in allergic rhinitis remains unknown, but may involve reductions in number of various mediator cells such as basophils, eosinophils, T-helper cells, mast cells, and neutrophils. In the nasal mucosa, nasal reactivity to allergens, and release of inflammatory mediators and proteolytic enzymes. Budesonide is very effective and quikly acting as it is rapidly and almost completely absorbed after oral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Thus, increases penetration, considering that the permeation is mainly transcellular, because of the hydrophilicity of the drug (Treffel et al, 1992). It has been previously reported that, increase in the plasticizer amount enhances the humidity absorption of the transdermal films, which is closely related to the permeability features of the water soluble drugs through transdermal films (Lade et al, 2011). This may explain the increase in the permeation rate (J μg/cm 2 /h) of L-CyS-HCl by increasing sorbitol concentration in the patches.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, increases penetration, considering that the permeation is mainly transcellular, because of the hydrophilicity of the drug (Treffel et al, 1992). It has been previously reported that, increase in the plasticizer amount enhances the humidity absorption of the transdermal films, which is closely related to the permeability features of the water soluble drugs through transdermal films (Lade et al, 2011). This may explain the increase in the permeation rate (J μg/cm 2 /h) of L-CyS-HCl by increasing sorbitol concentration in the patches.…”
Section: Resultsmentioning
confidence: 99%
“…The samples pulled from the vessel for 5 h with a 30 min interval. Each pulled sample was measured by UV-Spectroscopy at 268 nm λ max against blank [32,33] .…”
Section: Constant Release Studymentioning
confidence: 99%
“…[4] The development of techniques like virtual screening, pharmacophore generation, and fragment based drug discovery, advances in drug delivery has resulted in discovery of newer compounds and validation of newer targets and their proper administration to patients. [5,6] One of the major metabolic pathways found in bacteria is the fatty acid synthesis pathway and has become a popular target among medicinal chemist. In a recent development, the enzyme biotin carboxylase (BC) was found to be a very attractive target for inhibiting the Acetyl CoA carboxylase mediated reaction.…”
Section: Introductionmentioning
confidence: 99%